Comparison of Microleakage of a Self-adhesive Composite with a Conventional Flowable Composite and Resin Modified Glass Ionomer Cement in Class V Restorations - Maryam Mofidi; Razieh Hoseinifar; Fahime Shahrokhi; Mina Soltanianzadeh (Mashhad University of Medical Sciences, 2022)
Introduction: Self-adhering flowable composite resins were recently introduced to combine the merits of both adhesive and restorative technologies in one product. This study aimed to evaluate the microleakage of a self-adhering flowable composite in comparison with a conventional flowable composite and resin-modified glass ionomer cement in class V cavities. Methods: In this in vitro experimental study, class V cavities were prepared in the buccal and lingual surfaces of 20 sound human molars (40 cavities). The cavities were randomly divided into 4 groups (n=10) and restored with Vertise Flow self-adhering flowable composite in group A, Premise conventional flowable composite in group B, etched with 37% phosphoric acid and restored with OptiBond Solo Plus + Vertise Flow in group C, and Fuji II LC glass ionomer in group D. The specimens were thermocycled for 1000 cycles (5-55°C), immersed in 0.5% basic fuchsine dye solution for 24 h, sectioned, and observed under a stereomicroscope. Data were analyzed by SPSS software using the Kruskal-Wallis, Npar, and Wilcoxon signed rank tests (alpha=0.05). Results: The Kruskal-Wallis test showed that the degree of microleakage was not significantly different among different groups at the enamel margin (P=161) or the dentin margin (P=467). The Wilcoxon signed rank test revealed that the difference in microleakage between the dentin and enamel margins was significant within all four groups (P<0.05). Conclusion: The microleakage of self-adhesive composite, self-adhesive composite with separate etching and bonding, flowable composite, and glass ionomer cement was the same at both dentin and enamel margins.